AYURVEDIC MANAGEMENT OF ATROPHIC VAGINITIS WITH CERVICAL INTRAEPITHELIAL NEOPLASIA- A CASE REPORT (International Journal of Ayurveda and Pharma Research, 2020)
Vaginitis in postmenopausal women is termed as atrophic vaginitis, characterised by vaginal bleeding or spotting, vaginal discharge and discomfort or dryness in vulva. As the symptoms are not usually disclosed by women it may become chronic and can adversely affect the quality of life. In cervical intraepithelial neoplasia the squamous epithelium of cervix is replaced by the cells of varying degree of atypia. Even though CIN1 and CIN2 regress spontaneously, untreated CIN1 and CIN2 lesions may progress to invasive carcinoma. Ayurvedic management for the above conditions focuses on symptomatic relief and improvement of general health and immunity. Oral medication and Sthanika Chikitsa like Kshara Karma and Varthi play vital role in this. A 70 year old lady presented with complaints of burning sensation and itching over genital area. On examination haemorrhagic spots were observed on vaginal walls. She was sent to Early Cancer Detection Centre for cytological screening. The reports showed low grade sqamous intraepithelial lesion. She was managed with oral medications and Sthanika chikitsa. During follow up she was relieved from the symptoms like burning sensation and itching over genital area and vaginal discharge. Bleeding spots on vaginal walls were absent and cytology revealed a negative smear for intraepithelial lesion or malignancy. From this case report it is evidenced that Ayurvedic treatment modality is effective and successful for the management of Atrophic vaginitis with CIN.